Notes on African Biantinae with sexual dimorphism in leg II: five new Metabiantes species and redescription of Clinobiantes paradoxus (Opiliones: Laniatores: Biantidae) - Vanesa Mamani; Merlijn Jocqué; Abel Pérez-González (European Journal of Taxonomy)
This study deals with a group of African biantines harvestmen (Biantidae: Biantinae) that exhibit a unique sexual dimorphism on legs II, where the males possess a widened femur II and metatarsus II armed with ventral rows of triangular tubercles. Clinobiantes paradoxus Roewer, 1927, is redescribed and illustrated, including detailed illustrations and descriptions of the male and female genital morphology based on an examination of type material, with a lectotype designated herein. In addition, five new species of Metabiantes Roewer, 1915, also with dimorphic legs II, from tropical African countries are described and illustrated in detail: M. elongatus sp. nov., M. serratus sp. nov., and M. kivuensis sp. nov. from Democratic Republic of the Congo, M. herculeus sp. nov. from Tanzania, and M. kaurii sp. nov. from Mozambique. These findings enhance our knowledge within Metabiantes diversity, provide new insights into the distribution of Biantidae in tropical Africa, and highlight the morphological diversity associated with sexual dimorphism in the group.